Heart rate variability parameters indicate altered autonomic tone in subjects with COVID-19 - Gabriel Gruionu; Md Aktaruzzaman; Anita Gupta; Thomas V. Nowak; Matthew Ward; Thomas H. Everett (Scientific Reports, 2024)
Abstract COVID-19 is associated with long-term cardiovascular complications. Heart Rate Variability (HRV), a measure of sympathetic (SNS) and parasympathetic (PNS) control, has been shown to predict COVID-19 outcomes and correlate with disease progression but a comprehensive analysis that includes demographic influences has been lacking. The objective of this study was to determine the balance between SNS, PNS and heart rhythm regulation in hospitalized COVID-19 patients and compare it with similar measurements in healthy volunteers and individuals with cardiovascular diseases (CVD), while also investigating the effects of age, Body Mass Index (BMI), gender and race. Lead I ECG recordings were acquired from 50 COVID-19 patients, 31 healthy volunteers, and 51 individuals with cardiovascular diseases (CVD) without COVID-19. Fourteen HRV parameters were calculated, including time-domain, frequency-domain, nonlinear, and regularity metrics. The study population included a balanced demographic profile, with 55% of participants being under 65 years of age, 54% identifying as male, and 68% identifying as White. Among the COVID-19 patients, 52% had a BMI ≥ 30 compared to 29% of healthy volunteers and 33% of CVD patients. COVID-19 and CVD patients exhibited significantly reduced time-domain HRV parameters, including SDNN and RMSSD, compared to healthy volunteers (SDNN: 0.02 ± 0.02 s vs. 0.06 ± 0.03 s, p < 0.001; RMSSD: 0.02 ± 0.02 s vs. 0.05 ± 0.03 s, p = 0.08). In the frequency domain, both COVID-19 and CVD patients showed increased low-frequency (LF) power and lower high-frequency (HF) power compared to healthy volunteers (COVID-19 LF: 18.47 ± 18.18%, HF: 13.69 ± 25.80%; Healthy LF: 23.30 ± 11.79%, HF: 22.91 ± 21.86%, p < 0.01). The LF/HF ratio was similar in COVID-19 patients (1.038 ± 1.54) and healthy volunteers (1.03 ± 0.78). Nonlinear parameters such as SD1 were significantly lower in COVID-19 patients (0.04 ± 0.04 s vs. 0.08 ± 0.05 s, p < 0.01), indicating altered autonomic regulation. Variations in HRV were observed based on demographic factors, with younger patients, females, and non-white individuals showing more pronounced autonomic dysfunction. COVID-19 patients exhibit significant alterations in HRV, indicating autonomic dysfunction, characterized by decreased vagal tone and sympathetic dominance, similar to patients with severe cardiovascular comorbidities. Despite higher heart rates, the HRV analysis suggests COVID-19 is associated with substantial disruption in autonomic regulation, particularly in patients with specific demographic risk factors.